2016
DOI: 10.1515/jpem-2015-0397
|View full text |Cite
|
Sign up to set email alerts
|

Generic and disease-specific quality of life in adolescents with type 1 diabetes: comparison to age-matched healthy peers

Abstract: Background: This study aimed to evaluate the healthrelated quality of life (HRQoL) of adolescents with type 1 diabetes (T1DM) on the basis of the pediatric quality of life inventory™ (PedsQL™) generic and diabetes-specific modules, and to compare it to that of healthy peers. Methods: This retrospective case-control study involved 650 participants between ages of 13 and 19 years including 296 adolescents with T1DM from four diabetes centers and 354 healthy peers matched for age and gender from three different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
13
0
3
Order By: Relevance
“…Similar to the study of Kueh et al [ 28 ], in our study, self-care behavior of blood sugar control was correlated with the quality of life of patients with T2DM patients. Findings of the study also are in line with those of similar study performed by Lukacs et al [ 29 ] on T2DM patients that found an association between increased physical activity and higher quality of life. Therefore, it can be recommended that the health workers may promote physical activity among T2DM patients to help them improve their quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the study of Kueh et al [ 28 ], in our study, self-care behavior of blood sugar control was correlated with the quality of life of patients with T2DM patients. Findings of the study also are in line with those of similar study performed by Lukacs et al [ 29 ] on T2DM patients that found an association between increased physical activity and higher quality of life. Therefore, it can be recommended that the health workers may promote physical activity among T2DM patients to help them improve their quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Saleh et al (9), exercise had a significant relationship with all domains of QoL. Lukacs et al showed that increas- ing physical activity could improve the quality of life (24). Due to the direct connection between them, it is necessary to promote physical activity among T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, insulin dependence, together with multicomorbidity, makes diabetes management complex because of the need to achieve adequate control of blood glucose and other risk factors while preserving an acceptable quality of life for the patient. 2 To reduce the risk of invalidating complications and rationalize health expenditure through more modern and effective treatments, developing self‐management remains a key strategy. 3 In addition, insulin pump therapy and continuous glucose monitoring (CGM) have proven to be valuable aids, showing advantages in terms of glycemic compensation, risk of hypoglycemia, and quality of life.…”
Section: Introductionmentioning
confidence: 99%